Exploring the combined effects of sleep apnea and APOE-e4 on biomarkers of Alzheimer’s disease - Turner, Arlener D.; Locklear, Clarence E.; Oruru, Daisha; Briggs, Anthony Q.; Bubu, Omonigho M.; Seixas, Azizi (Frontiers in Aging Neuroscience, 2023)
Objective: We determined the interactive associations of apolipoprotein-e4 (APOE-e4), and obstructive sleep apnea (OSA) on biomarkers of Alzheimer’s disease, and examined racial/ethnic differences of this association. Methods: We used data from the National Alzheimer’s Coordinating Center Uniform Dataset (NACC UDS). All participants undergo annual observations, including demographic survey, neuropsychological test battery, blood draw (with genotyping), and a clinical evaluation with medical and cognitive/dementia status assessment, while a subset of participants have cerebrospinal fluid (CSF) biomarkers and neuroimaging data. AD biomarkers were characterized as the presence of abnormally low amyloid in CSF, via validated Aβ42 cut off protocols, and total segmented hippocampal and white matter hyper intensities (WMH) volume. While clinical markers were characterized via the Montreal Cognitive Assessment (MOCA). Results: Biomarker and clinical marker data were derived from 1387 participants at baseline (Mean age=69.738.32; 58.6% Female; 13.7% Black/African American), 18.4% of the sample had OSA, and 37.9% were APOE-e4 carriers. Our results confirmed previous reports that OSA and APOE-e4 were independently associated with AD through abnormal levels of amyloid (F(1,306)=4.27; p=0.040; F(1,285)=60.88; p<.000, respectively), WMH Volume (F(1,306)=4.27; p=0.040; F(1,285)=60.88; p<.000, respectively), and MoCA scores (F(1,306)=4.27; p=0.040; F(1,285)=60.88; p<.000, respectively). No significant interaction between OSA and APOE-e4 relative to amyloid emerged, however, race stratified analyses indicated the interaction of OSA and APOE-e4 was significantly associated with WMH and hippocampal volume in Black/African American, but not White participants. Conclusion: OSA and APOE-e4 are interactively associated with WHM in Black/African Americans. This interaction may partially explicate increased levels of risk in this population